Can Pharmacists’ Counseling Improve the Use of Inhalers and Quality of Life? A Prospective “Pre” and “Post” Education Analysis in Mardan, Pakistan - Gul, Sumaira; Rehman, Inayat Ur; Goh, Khang Wen; Ali, Zahid; Rahman, Aziz Ur; Khalil, Asad; Shah, Ismail; Khan, Tahir Mehn; Long, Chiau Ming * (Dove Press, 2023)
ntroduction: Asthma is one of the common major non-communicable respiratory diseases, and is associated with a lower health-related quality of life (QOL). Poor inhalation is a significant contributing factor to poor control of asthma. Community pharmacist has a vital role to play in assisting patients and ultimately improving their asthma conditions through the use of inhalers.